Effects of Grain Boundaries at the Electrolyte/Cathode Interfaces on Oxygen Reduction Reaction Kinetics of Solid Oxide Fuel Cells. (7th March 2017) - Choi, Mingi; Koo, Ja Yang; Ahn, Minwoo; Lee, Wonyoung
Abstract : We systematically investigated the effects of grain boundaries (GBs) at the electrolyte/cathode interface of two conventional electrolyte materials, i.e., yttria‐stabilized zirconia (YSZ) and gadolinia‐doped ceria (GDC). We deposited additional layers by pulsed laser deposition to control the GB density on top of the polycrystalline substrates, obtaining significant improvements in peak power density (two‐fold for YSZ and three‐fold for GDC). The enhanced performance at high GB density in the additional layer could be ascribed to the accumulation of oxygen vacancies, which are known to be more active sites for oxygen reduction reactions (ORR) than grain cores. GDC exhibited a higher enhancement than YSZ, due to the easier formation, and thus higher concentration, of oxygen vacancies for ORR. The strong relation between the concentration of oxygen vacancies and the surface exchange characteristics substantiated the role of GBs at electrolyte/cathode interfaces on ORR kinetics, providing new design parameters for highly performing solid oxide fuel cells. Abstract :